2018
DOI: 10.1353/ol.2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Plural Word hire in Alorese: Contact-Induced Change from Neighboring Alor-Pantar Languages

Abstract: This article discusses the plural word hire in Alorese, an Austronesian language spoken on the islands of Alor and Pantar, in eastern Indonesia. Following the methodological requisites for contact-induced change, I claim that the plural word hire emerged through contact with Papuan Alor-Pantar languages, because (i) Alorese was and still is spoken in close contact with Alor-Pantar languages; (ii) Alorese and the neighboring Alor-Pantar languages share the presence of a plural word, and their plural words have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The legend about the founding of Pandai is also the first of two legends reported in Lemoine (1969) and cited in Barnes (1973Barnes ( : 86, 2001 and Rodemeier (2006). Today, it is still part of the oral history of the Alorese: in 2016, Francesca Moro recorded a story in Pandai in which the current king of Pandai, Rajab Suleiman Abu Bakar, tells the same legend about a Javanese king who came to Pantar and founded the village of Pandai, dating his arrival at 1,310 AD (Moro 2018). The legend recounts that two Javanese brothers, Aki Ai and his younger brother Mojopahit, sailed to Pantar, where Aki Ai treacherously abandoned Mojopahit.…”
Section: Dating the Migration Of Pre-alorese To Pantar Islandmentioning
confidence: 99%
See 2 more Smart Citations
“…The legend about the founding of Pandai is also the first of two legends reported in Lemoine (1969) and cited in Barnes (1973Barnes ( : 86, 2001 and Rodemeier (2006). Today, it is still part of the oral history of the Alorese: in 2016, Francesca Moro recorded a story in Pandai in which the current king of Pandai, Rajab Suleiman Abu Bakar, tells the same legend about a Javanese king who came to Pantar and founded the village of Pandai, dating his arrival at 1,310 AD (Moro 2018). The legend recounts that two Javanese brothers, Aki Ai and his younger brother Mojopahit, sailed to Pantar, where Aki Ai treacherously abandoned Mojopahit.…”
Section: Dating the Migration Of Pre-alorese To Pantar Islandmentioning
confidence: 99%
“…10 However, if its segment inventory 9. Moro (2018) revealed that the plural word hire in Alorese emerged through contact with non-Austronesian languages, constituting a complexification of Alorese grammar with bilingual children as agents (2018: 194).…”
Section: Alorese Was Acquired By Adult Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case with Alorese, an Austronesian language spoken on the islands of Alor and Pantar, which has been in contact with neighbouring Papuan languages for about 600 years (Klamer 2011). There is evidence that Alorese was learned as an L2 by many Papuan speakers (Klamer 2012(Klamer , 2020Moro 2018Moro and Fricke 2020). Studying the on-going changes in the L2 of speakers today allows us to make inferences about the changes which have happened in the past and helps us reconstruct the history of Alorese and the reasons it has the structures is has today (an impoverished morphology, genealogically unexpected grammatical patterns, et cetera).…”
Section: Changes In Second Language (L2) Under Influence Of First Language (L1)mentioning
confidence: 99%
“…For plural marking on nouns using other means, a few scattered cases are attested within the Flores-Lembata group. Alorese has a plural word which has emerged as a consequence of contact-induced grammaticalization involving the neighbouring TimorAlor-Pantar languages (Moro 2017). Hewa, a Sika variety, has a plural word ahan only used for human referents (Fricke 2014: 14).…”
mentioning
confidence: 99%